How Cognitively Guided Instruction Model Develop Mathematical Knowledge For Teaching? - Mery Noviyanti (International Journal of Education, Information Technology, and Others, 2020)
This research aims at obtaining an overview of how the Cognitively Guided Instruction (CGI) model develops Mathematical Knowledge for Teaching of Early Childhood Education (ECE) teachers. The participants of the research were five kindergarten teachers in one district in West Java, Indonesia, who were purposively selected. The research design employed is a qualitative case study approach and thematic analysis to process and analyze the data. The findings show that the Cognitively Guided Instruction (CGI) model applied in the Professional Development Program (PDP) can develop Mathematical Knowledge for Teaching (MKT) of Early Childhood Education (ECE) teachers. This model is considered to be useful as the intervention provided can develop teachers' knowledge properly, resulting in the improvement of teachers' MKT.